Sketsa Kebudayaan Lembaga Pendidikan Islam - Hendro Widodo (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2017)
The development of pesantren, schools and madrasah is a form of culture. They have dynamism in the society development. Pesantren, schools, and madrasah are also a manifestation of the lives of people or groups of people in the educational environment. The development of pesantren, school and madrasah as a unity of the development of educational institutions in Indonesia are interconnected with each other, so the cultural development of the three educational institutions can be seen from the cultural model proposed by van Peursen, covering mythological, ontological and functional phases. This article reveal and explore the development of pesantren, schools, and madrasah in cultural reviews. The researcher used cultural theories of van Peursen and Auguste Comte.Â Keywords: Pesantren, School, Madrasah, Culture